ANALISIS RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) RAWAT JALAN DI RSUD DR. MOEWARDI SURAKARTA - Wahyuningsih Marda Sari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Acute respiratory infection (ARI) has become a common disease that we often encounter in society, especially in children under five and is still a major health problem in Indonesia. The irrational use of antibiotics causes many problems that arise and is a global threat to public health, especially in bacterial resistance to antibiotics. This study aims to determine the rationality of using antibiotics which includes the right indication, the right drug, the right patient and the right dose based on the Pharmaceutical care guidelines, 2005 and to find out the rationality of using antibiotics using the Gyssens method compared to the PMK guidelines, 2021 and DIH, 2019.The research method used is descriptive method and data collected retrospectively. The population of this study was all outpatient data with a diagnosis of acute respiratory infection at Dr. Moewardi Surakarta in 2022. The sample for this study was all medical record data of ARI patients during January - December 2022 adjusted for inclusion criteria.The results of the rationality of the use of antibiotics obtained the right indication (51%), the right dose (35%), the right drug (51%), and the right patient (100%) and the results of the rationality of using antibiotics using the Gyssens method showed the results for category 0 (32%) , category IIa (4%), category IIb (3%) and category V (61%).Keywords – Antibiotics, Acute Respiratory Infections, Gyssens Method, Rationality